Alfalfa and silage maize intercropping provides comparable productivity and profitability with lower environmental impacts than wheat–maize system in the North China plain. (January 2022) - Xu, Ruixuan; Zhao, Haiming; Liu, Guibo; Li, Yuan; Li, Shoujiao; Zhang, Yingjun; Liu, Nan; Ma, Lei
Abstract: CONTEXT: The sustainability of winter wheat ( Triticum aestivum L.) − summer maize ( Zea mays L.) rotation (W − M), which is commonly practiced in the North China Plain (NCP), is threatened by severe groundwater deficits and environmental pollution due to excessive nitrogen (N) applications. OBJECTIVE: Considering the need for protein-rich forages by local livestock operations and the environmental benefits of growing perennial legumes, we propose that an alfalfa ( Medicago sativa L.)-based system is worth introducing for field practice in the NCP. METHODS: An integrated evaluation was used in this four-year study to compare the agronomic, economic, and environmental performances of the following four cropping patterns: alfalfa monoculture (AA), alfalfa and silage maize intercropping with or without N input which is designed for local climate condition, maize monoculture with or without N input which is much-discussed as a resources-saving substitution and commonly practiced W − M. RESULTS AND CONCLUSIONS: W − M obtained the highest aboveground dry matter (DM) productivity ( P < 0.05) based on the highest irrigation water and N fertilizer consumption ( P < 0.05) which caused considerable soil mineral N (Nmin) accumulation. The production cost of maize monoculture was the lowest as well as the DM yield, nitrogen accumulation and the net revenue compared with other systems ( P < 0.05), moreover, there was a great risk of N losses during the offseason period. The alfalfa and silage maize intercropping with a low N input (120 kg ha −1 which is close to local practice for maize season) achieved 26.6%–34.9% more DM yield compared with AA and maize monoculture, and 12.5%–163.9% more N output compared with W − M and maize monoculture during four experimental years with same total economic revenue as W − M and AA did. The N input in alfalfa and silage maize intercropping dramatically improved the system productivity by assisting intercropped maize growth while did not lead to excessive Nmin accumulation within 0–210 soil layer compared with the intercropping system without N addition. The planting of alfalfa would not affect the water storage in the 0–60 soil layer after maize harvesting each year. For the effects of interspecific competition, the production of the intercropped alfalfa and maize was significantly decreased in 2020 and a three-year period of production is recommended for optimal use of the alfalfa and silage maize intercropping. SIGNIFICANCE: Alfalfa and silage maize intercropping with an appropriate N input, which acquired comprehensive performances in terms of productivity, environmental impacts as well as economic profits, would be an optimal alternative system in the NCP. Graphical abstract: The alfalfa and silage maize intercropping with an appropriate N input (A + M), which achieved high dry matter yield, nitrogen uptake and net revenue with the lowest irrigation water and nitrogen fertilizer use, would be an optimal alternative system in the North China Plain. Unlabelled Image Highlights: The wheat–maize rotation (W – M) in the North China plain is profitable but has inevitable negative environmental impacts. Alfalfa and maize intercropping (A + M) was proposed for the high protein productivity and the adaptability to climate. The agronomic, economic, and environmental performances were compared among A + M, W – M, and monoculture systems. A + M was more productive than monoculture, and consumed lower groundwater and nitrogen than W–M without net revenue loss. A + M would be an optimal alternative system in the North China Plain for its comprehensive performances.